Islamic Civilizations From The Lense Of Advanced Scientific Legacies: Insights From Kitab Tabaqat Al-umam - Mohd Zamrus Mohd Ali; Musa Mohamad; Ahmad Fuad Mohamad Amin; Ahmad Bazli Ahmad Hilmi; Zulkarnin Zakaria (Wise Press UK, 2024)
Non-Indexed Publication